Clinician approaches to communicating a dementia diagnosis: An interview study. - Easton N Wollney; Carma L Bylund; Noheli Bedenfield; Monica Rosselli; Rosie E Curiel-Cid; Marcela Kitaigorodsky; Ximena Levy; Melissa J Armstrong (PLoS ONE, 2022)
Background Individuals with cognitive impairment and their families place a high value on receiving a dementia diagnosis, but clinician approaches vary. There is a need for research investigating experiences of giving and receiving dementia diagnoses. The current study aimed to investigate clinician approaches to giving dementia diagnoses as part of a larger study investigating patient, caregiver, and clinician experiences during the diagnosis encounter. Method Investigators conducted telephone interviews with Florida-based clinicians who give dementia diagnoses either rarely or commonly. Interviews employed a semi-structured interview guide querying communication practices used by clinicians when giving dementia diagnoses and how clinicians learned to give dementia diagnoses. Investigators used a descriptive qualitative design to conduct a thematic analysis of data. Results Fifteen Florida-based clinicians participated, representing diverse backgrounds related to gender, race/ethnicity, specialty, and practice setting. Participants reported using patient- and family-centered communication practices including checking patient understanding, communicating empathically, and involving family members. Some clinicians explicitly asked patients and/or family members about their preferences regarding diagnosis disclosure; many clinicians tailored their disclosure based on patient and family characteristics or reactions. Some clinicians reported using specific diagnoses, while others used general terms such as "memory disorder." Clinicians reported positively framing information, including instilling hope, focusing on healthy behaviors, and discussing symptom management. Finally, clinicians provided patient/family education and arranged follow up. Clinicians reported learning approaches to dementia diagnosis disclosure through formal training and self-education. Conclusions Diverse Florida-based clinicians described dementia disclosure practices largely consistent with published guidance, but clinicians varied on approaches relating to soliciting patient disclosure preferences and terminology used. Clinicians caring for diverse populations described that cultural background affects the disclosure process, but more research is needed regarding this finding and best practices for individuals from different backgrounds.